SEQUENTIAL KRIGING DALAM GEOSTATISTIKA - , MUHAMAD AJI IKHSANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kriging is a computation technique to calculate estimates of a variable teregional the approach that the data being analyzed is considered as a realization of a random variable, and overall random variable is analyzed to form a random function using a structural model of variogram. Semivariogram semivariogram isotropy is affected by the distance between sample points. Sequential kriging is equivalent to simple kriging. Data set (data set) is divided into several subsets and each subset allows a single data. In the availability of additional data, sequential estimators improve previous estimates using a linear weighting of new data and the previous estimate of a location.